1988
DOI: 10.1177/0272431688081001
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Conflictual Family Issues by Adolescent Pubertal Status, Gender, and Family Member

Abstract: The purpose of this study was to describe domains of family conflict and to examine variations in these domains by adolescent pubertal status, gender, and status as a family member. Sixty-three intact family triads completed an instrument designed to assess pubertal status and the Issues Checklist. Principal Factor Analysis with Varimax rotation resulted in the retention of seven factors accounting for 78.52 percent of the variance. Separate Stepwise Regression analyses were conducted for each factor (using fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…The IC is a 44-item list of issues that may be areas of disagreement between parents and adolescents. Scores have been found internally consistent and validity has been supported in numerous studies (Prinz et al, 1979;Robin & Weiss, 1980;Robin, 1981;Foster, Prinz, & O'Leary, 1983;Robin, Koepke, & Nayer, 1986;Papini & Sebby, 1988;Robin & Foster, 1989;Grace, Kelley, & McCain, 1993). In particular, the scores that tap intensity of issues discriminate strongly between distressed and nondistressed mothers and adolescents (Robin & Weiss, 1980).…”
Section: Instrumentmentioning
confidence: 85%
“…The IC is a 44-item list of issues that may be areas of disagreement between parents and adolescents. Scores have been found internally consistent and validity has been supported in numerous studies (Prinz et al, 1979;Robin & Weiss, 1980;Robin, 1981;Foster, Prinz, & O'Leary, 1983;Robin, Koepke, & Nayer, 1986;Papini & Sebby, 1988;Robin & Foster, 1989;Grace, Kelley, & McCain, 1993). In particular, the scores that tap intensity of issues discriminate strongly between distressed and nondistressed mothers and adolescents (Robin & Weiss, 1980).…”
Section: Instrumentmentioning
confidence: 85%
“…Whereas pubertal changes in males tend to be valued by society and by males, pubertal changes in girls (i.e., increased body fat) are often devalued by society and by girls themselves (Dorn, Crockett, & Petersen, 1988;Nolen-Hoeksema, & Girgus, 1994;McCarthy, 1990). Consistent with this, early-maturing boys have been found to have higher than average weight satisfaction, whereas girls show a reverse pattern, with early maturation associated with lower weight satisfaction (Alsaker, 1992;Dorn et al, 1988) and heightened risk for depression (Alsaker, 1992;Papini & Sebby, 1988;.…”
mentioning
confidence: 88%
“…In a short-term longitudinal study of firstborn adolescents, Steinberg (1988) found that ratings of puberty negatively predicted scores on measures of closeness that tapped cohesion and calm communication. Third, conflict between parents and adolescents seems to increase during early adolescence and then decreases by late adolescence (Paikoff & Brooks-Gunn, 1991;Papini & Sebby, 1988). Although increased conflict does not seem to have a deleterious effect on parents' and adolescents' reports of overall relationship quality (Hill & Holmbeck, 1987), such conflict may amount to what stress researchers call daily hassles and may contribute to parents' perceptions that adolescence is a difficult developmental period (Arnett, 1999).…”
Section: Parents' Perceptions Of Relationship Changementioning
confidence: 99%